VO2/ATO nanocomposite thin films with enhanced solar modulation and high luminous transmittance for smart windows. Issue 11 (1st June 2022) - Song, Jiaxin; Zhao, Yiwei; Sun, Lan; Luo, Qiaomei; Xu, Huiyan; Wang, Chen; Xin, Hongqiang; Wu, Wenshuo; Ma, Fei
Abstract: Developing an economic, facile strategy to prepare high-efficiency VO2 -based thin films is critical to thermochromic smart windows. It is still challenging to simultaneously achieve high luminous transmittance ( T lum ) and large solar modulation ( ΔT sol ). In this paper, the composites of VO2 nanoparticles and antimony-doped tin oxide (ATO) nanoparticles are prepared to significantly boost the overall performances of the films. As compared with pristine VO2, the T lum value of the composite films is substantially increased from 30.91% to 84.35% by 170%, while a suitable ΔT sol value of 11.57% is almost maintained. Furthermore, an optimized overall performance of T lum (60.14%) and ΔT sol (20%) is achieved. The excellent optical properties are closely related with the dispersive small particles and widened optical band gap. The results provide an effective strategy for enhanced performances of smart windows.